The Baltimore City Code: Comprising the Statutes and Ordinances Relating to the City of Baltimore, at 171 - Art. XVI, Section 27 (1869) § 27 - (:unkn) unknown (General Publisher, 1869)
If the said board of police shall have reason to believe that in the neighborhood of any election polls in the said city or elsewhere, within any election precinct of the same, there is any depot or collection of fire arms or other weapons or ammunition intended to be used for the purpose of intimidating or injuring voters, or interfering with the freedom or peace of any election then pending or approaching, it shall be the duty of said board to apply to the Criminal Court, or some justice of the peace of said city, for a warrant, on proper oath, to search the premises, and the said court or justice shall issue the same without delay, and shall cause the said arms, weapons and ammunition, if found, to be seized and delivered to said board, to be detained until the day after the returns of said election shall have been made, and until the same shall be disposed of by law.
--
Keywords: CARRY - CERTAIN PUBLIC PLACES